Pengaruh Relaksasi Otot dalam Menurunkan Skor Kecemasan T-Tmas Mahasiswa Menjelang Ujian Akhir Program di Akademi Keperawatan Notokusumo Yogyakarta - Suyamto Yayi Suryo Prabandari, Carla Raymondalexas Marchira (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Anxiety is a disorders that has symptoms of heart, dizzy, wet palm and foot or emotional disorders such as discomfort feeling, difficult to concentrate, worried, exhaustness, insomnia, less appetite. This condition often occurred in students of Nursing Academy (Akper) of Notokusumo Yogyakarta when they are facing final examination. This is obtained from a preliminary research that was conducted by giving question on the condition experienced by the students of Akper Notokusumo Yogyakarta regarding their worryness in facing the examination with subject of 50 students that was held on the 5th – 8th of October 2007.Objective: This research was aimed to find out the influence of muscle relaxation in decreasing the TMAS anxiety score of students in facing their final examination.Method: This was a quasi experimental design with randomized control group pre test and post test design that was research subjects who were classified into two groups that were treatment group that was located in Akper Notokusumo with 100 students and control group that was located in Akper Karya Bhakti Husada Bantul with subjects of 50 students. Both of the groups were given pre test before given treatment, and yet, one group was given post test after treatment while the other group was given post test without treatment. The intsrument being used was Taylor Manifest Anxiety Scale (TMAS). The analysis being used to examine the difference of treatment and control group was conducted with independet sample t test with significance level of p = 0.05.Result: The result of the research showed that there was a decreasing on anxiety from pre test to post test. In control group, there was no decreasing of anxiety from pre test to post test even there was an improvement during post test.Conclusion: Relaxation had influence in decreasing anxiety of student of Nursing Academy of Notokusumo Yogyakarta as treatment group and the result was lower during post test compared to pre test.Keywords: anxiety, relaxation, student